METHODOLOGICAL SPECIFICITY OF PEDOLOGY - Онопрієнко, В. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The article describes features and evolution of the methodological bases of the soil science under the influence of V. V. Dokuchaeva, V. I. Vernadsky, B. B. Polynov, Ya.V. Samoilov. The author discusses the formation of pedology as a soil science. In particular, a special role of methods and methodology of such fundamental sciences as biology, geology, chemistry and geography in the pedology is noted. The relevance of the methodological aspects of soil science in solving new topical problems of soil science is justified. The aim of the article is to study the methodological aspects of the soil science at the present stage of its development. The task of the article is to assess the prospects of the methodological concept of studying the concentration functions of the soil cover. Research methods are systemic, interdisciplinary, cultural-historical, socio-cultural, and comparative ones in their dialectical interrelations. Research results. A geological object should be interpreted as a system with the genetic structure, the integrity of which is ensured by the historical trajectory of the system. The specificity of an object is the result of synthesis in the process of evolution of various natural interactions. The historical approach to developing objects is implemented using the method of actualism, revealing the invariant structure of geological processes and the form of modeling method. The new program of science development should combine the use of ideas, methods, models of theoretical natural science and the adjustment and improvement of historical reconstruction tools. Such a program is aimed at establishing the unity of the spatial structure and genesis of geological objects and extending the functions and areas of application of the system-structural method. The holistic characteristics of geological processes cannot be adequately reflected without the use of tools and methods of a systematic approach based on non-causal determination, on the analysis of relations between coexistence and correlation. Discussion provides a comparative description of various ideas about soil science. The main threat to the harmony of the methodological systems of genetic soil science and geological sciences is noted to be significant changes in the structure of the latter: at the end of the XX-th c. the basis of a well-founded V. I. Vernadsky and rapidly developing biogeochemistry becomes dominative. Conclusion. The methodological concept of studying the concentration functions of the soil cover has not yet been sufficiently implemented in soil science, but it is certainly prospective. The fundamental function of the soil is shown to be realized through ensuring the participation of the soil in the regulation of specific mechanisms of biospheric processes.